Application Of The Promotional Mix Strategy To Attract Travelers During The Covid-19 Pandemic - Afif, Fuadi; Adellia Yuke Larasati; Hari Rachmadi (Media Wisata, 2023)
Located in the city of Yogyakarta, Muki Travel is a travel agency business that is growing. As it develops, Muki Travel offers tourism services like selling vacation packages and meeting lodging needs. Specifically, during the COVID-19 pandemic, Muki Travel must take new steps or use the most current strategies to draw tourists during the pandemic. This study aims to determine how the promotion mix is implemented. Both field research and library research are methods used to obtain data. According to a survey conducted at Muki Travel, which used five different techniques of the promotion mix strategy, two of them—advertising and sales promotion methods—are more prevalent than the other five.